Redefining Our Understanding of The Impact of Firearm-Related Injury in the State of Georgia: A White Paper by the Violence Prevention Task Force of IPRCE - Omar Danner; Lauren Hudak; Rana Bayakly; Carol Koplan; Alexander Kelly; Sharon Nieb; Sheryl Heron (Georgia Southern University, 2020)
Abstract Background: Firearm-related injury is a crisis that afflicts vulnerable populations of all ages, ethnicities, races and gender. The purpose of this white paper is to delineate the impact of firearm-related violence on the health and well-being of citizens and communities across Georgia based on the available literature and data. The aim of this white paper is to examine and characterize the currently available data on the impact of firearm violence and injury from a statewide perspective, principally as it relates to the National Violent Death Reporting System (NVDRS) report for Georgia. Materials and method: We performed a literature review to analyze data obtained through the the Web-based Injury Statistics Query and Reporting System (WISQARS™) and NVDRS. We used the data to characterize the types and extent of firearm injuries and deaths in the U.S. and Georgia. Results: We identified an overall mortality rate of 27% for all-types of firearm injuries. The estimated average annual age-adjusted firearm injury rate was 31.5 per 100,000 people. The case fatality rate for suicide due to firearm injury notably had the highest gun-related mortality rate by greater than 6-fold. Furthermore, from 2015 to 2016, the national mean annual case fatality rate was 84% for firearm-related suicide according to 2017 CDC report.Conclusion: Greater investment into research, education and prevention of gun-related violence among citizens in the state of Georgia is necessary. Although firearm-related aggravated assault due to interpersonal violence is common, the case fatality rate due to suicide has a greater than 6-fold higher rate of death.